2015
DOI: 10.3233/jpd-150594
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of Parkinson’s Disease in a Multiethnic Urban Asian Setting

Abstract: This is the only study on public knowledge regarding PD in Asia. Important gaps in knowledge were evident, which could present a barrier to early diagnosis and appropriate treatment of PD. This highlights the need for targeted education campaigns and further research in this area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…Previously, few surveys have been conducted to assess the knowledge, attitudes and perceptions about PD [ 2 - 5 ]. In Asian countries, patients have the misconception that PD is currently curable and usually familial [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, few surveys have been conducted to assess the knowledge, attitudes and perceptions about PD [ 2 - 5 ]. In Asian countries, patients have the misconception that PD is currently curable and usually familial [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, few surveys have been conducted to assess the knowledge, attitudes and perceptions about PD [ 2 - 5 ]. In Asian countries, patients have the misconception that PD is currently curable and usually familial [ 2 ]. The results of Jitkritsadakul et al [ 3 ] showed that recruitment of patients at a younger age (< 60 years old), female gender, and higher disease duration (> 4 years), were identified as predictors of a higher level of PD knowledge among patients.…”
Section: Discussionmentioning
confidence: 99%
“…This may explain findings showing that Black patients under-report their symptoms and could account for some differences in the severity of PD seen [167]. In a multi-ethnic study of PD knowledge in Asia, significant differences in PD knowledge according to ethnicity were found; people of Chinese ethnicity were more aware of the non-motor symptoms of PD compared to Malay people (p < 0.001) and Chinese people were more likely than Indians to be aware that not all patients with PD have a tremor (p = 0.009) [168].…”
Section: Under-reporting Of Symptomsmentioning
confidence: 99%
“…However, there are published studies on this topic from Asia, Europe, USA, and Australia. [6910111213] In our study, we introduced a previously validated questionnaire to the public ( n = 2609). We found the general knowledge of the public was reasonably well with common misperceptions (for example, tremor as the universal feature of PD among 79.15% of respondents).…”
Section: Discussionmentioning
confidence: 99%
“…[9] A study in Malaysia reported that 49.8% of participants believe that there is a cure for PD and 41.4% thought that it is usually familial. [10]…”
Section: Introductionmentioning
confidence: 99%